PELATIHAN PEMBUATAN VIRGIN COCONUT OIL (VCO) DENGAN METODE BASAH KEPADA IBU-IBU PKK NEGERI KILANG SEBAGAI UPAYA PENINGKATAN NILAI EKONOMIS BUAH KELAPA - Serly J. Sekewael; Netty Siahaya; Hellna Tehubijuluw; Imanuel Berly Delvis Kapelle; Fensia Analda Souhoka; Linda Lattuputty (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2022)
The training for making Virgin Coconut Oil (VCO) with the wet method has been carried out for the PKK women of Negeri Kilang, South Leitimur District, Ambon City. VCO with the wet method using liquid coconut milk as raw material. The oil from this liquid coconut milk is extracted by precipitation. After that, the oil that has been separated from water and other solids is transferred to be filtered to make it clear. The steps of this training activity are carried out in three stages, namely preparation, implementation, and evaluation. In the preparatory stage, the team conducted a preliminary survey to determine the field conditions, and the place to be used; and to prepare a plan for the activities to be carried out. Next, the team prepares materials and equipment that will be used in making VCO. At the implementation stage, the team conducted counseling for PKK women by delivering material on how to make VCO and the benefits of VCO in the health sector. Then proceed with the manufacture of VCO with the wet method. In this activity, all participants were trained on how to make VCO, starting from the procedure for making coconut milk from coconuts to forming VCO. The third stage, namely the evaluation stage, is carried out to measure the level of success of the activities that have been carried out. The output produced from this activity is a creative product of coconut plants, namely VCO which has been made by women of PKK Negeri Kilang to be used daily.